O mundo inimigo. Inferno provisório Vol. II, de Luiz Ruffato: a representação dos trabalhadores das páginas para as telas - Rodrigues, Reginaldo de Souza (2020)
In O mundo inimigo (2005), volume II of Inferno provisório series of novels, by Luiz Ruffato, we may find a wide variety of anonymous characters, unemployed workers, poor migrants, all residents of a country town of Minas Gerais, Cataguases and, among them, the history and conflicts of two friends who grew up together, but were distanced due to their individual choices The present dissertation proposes to analyze how Villamarim adapted Ruffato's kaleidoscopic prose into screen, in which past and present intertwine causing conflicts between the individual and the social, revealing how the social transformations of a small city are reflected in its subjects’ lives., as well as emigration operates in characters’ feeling of belonging, based upon the understanding of the role of the literature produced by the author, his position as an organic intellectual of his class and how cinema translates such positions that question the status quo in contemporary society, focusing on the conflicting relationship between the characters Gildo and Luzimar. First, we have reinforced the theoretical aspects of what we understand by Intersemiotic Translation, according to Roman Jakobson (1991), Antoine Berman (2002) and Plaza (2001). Then, we have demonstrated the reverberations of Intersemiotic Translation in Brazilian literature and cinema, at a time in which the dialogue between these two fields of studies has become quite productive, considering the varied cinematographic or television versions of works from Brazilian literature, thus expanding, public access to audiovisual readings of classic and contemporary works. Subsequently, we discuss how the Brazilian working class has been historically represented in Brazilian literature and cinema, and how the author of the novel studied here shows himself on this issue, and on the role of intellectuals in the public debate about art and its social role. After that, we have looked for the concepts of “subaltern” and “place of speech”, by Gayatri Spivak (2010), in order to understand the political dimension of Luiz Ruffato's literary project, which encompasses mainly, in the work Inferno provisório, a potent portrait of the Brazilian proletariat from the second half of the 20th century to the beginning of the 21st century. Finally, we establish the possible relationships between Ruffato's work and its adaptation for cinema, concluding that important issues raised by the writer are present in Villamarim's cinematographic work.